2017
DOI: 10.1186/s12875-017-0599-z
|View full text |Cite
|
Sign up to set email alerts
|

Using self-reported data on the social determinants of health in primary care to identify cancer screening disparities: opportunities and challenges

Abstract: BackgroundData on the social determinants of health can help primary care practices target improvement efforts, yet relevant data are rarely available. Our family practice located in Toronto, Ontario routinely collects patient-level sociodemographic data via a pilot-tested survey developed by a multi-organizational steering committee. We sought to use these data to assess the relationship between the social determinants and colorectal, cervical and breast cancer screening, and to describe the opportunities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
53
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 41 publications
1
53
0
2
Order By: Relevance
“…We identified potentially eligible patients as of March 31, 2015 using data from a provincial registry and our practice EMR as described previously. 12,15 Eligibility determination was consistent with provincial guidelines. 16 Women aged 21 to 69 years and 50 to 74 years were eligible for cervical and breast cancer screening, respectively.…”
Section: Study Design and Participantsmentioning
confidence: 65%
“…We identified potentially eligible patients as of March 31, 2015 using data from a provincial registry and our practice EMR as described previously. 12,15 Eligibility determination was consistent with provincial guidelines. 16 Women aged 21 to 69 years and 50 to 74 years were eligible for cervical and breast cancer screening, respectively.…”
Section: Study Design and Participantsmentioning
confidence: 65%
“…6 Even with self-reported data, up to 25% of some SDH variables can be missing for some cohorts. 20 Widespread missing data may artificially create more variation in the revisit estimates. 21 To alleviate this problem during statistical analysis, many researchers exclude SDH variables with high levels of missingness, 6,20,21 use multiple imputation mechanisms, 8,22 or use other weighting procedures.…”
mentioning
confidence: 99%
“…20 Widespread missing data may artificially create more variation in the revisit estimates. 21 To alleviate this problem during statistical analysis, many researchers exclude SDH variables with high levels of missingness, 6,20,21 use multiple imputation mechanisms, 8,22 or use other weighting procedures. 23 While these methods are sound, there is a need to gather a more relevant SDH history on patients to understand the significance of SDH across the care continuum, including transitioning to care at home.…”
mentioning
confidence: 99%
“…Decisions around which data to collect are determined by the priorities, and subsequent informational needs, of the health system in question. For example, considerable research is devoted to which data are necessary to improve care continuity and chance of recovery(24), reduce rate of readmission(32), or improve population rates of participation preventative practices(6). The landscape of SDOH metrics and valid associations therefore changes across environments based on situated needs.…”
mentioning
confidence: 99%
“…One of the two articles from Canadian study sites provides an example of how regional information management contexts influence SDOH screening. The authors stated that their survey design did not initially follow the principles of Ownership, Control, Access, and Possession (OCAP®), which governs research concerning Canada's Indigenous populations(38), and thus influenced how the authors reported study findings(6). This observation points to the need for additional research on contextually driven data collection methods, as well as further investigation into how recommendations from leading health organizations (e.g.…”
mentioning
confidence: 99%